SKIN MICROBIOME AND ITS IMPLICATIONS FOR DERMATOLOGICAL DISEASES: NEW THERAPEUTIC PERSPECTIVES - Rezende, Danielle; Pedro do Valle Varela, João; Pinheiro Amantéa Vilela, Júlia; Brito Teixeira, Izabel; Maria de Almeida Batista, Ana; Folz Rossini, Gustavo; Machado dos Reis, Yago; Moreira Mendes, Hadija; Raasch Jacobsen, Karina; Nobre da Silva Ramos, Bruna; Costa Buzatto, Nathalia; Rocha Santório, Éric; et al. (Health and Society, 2025)
The skin microbiome, made up of a vast diversity of microorganisms, including bacteria, fungi and viruses, plays a crucial role in maintaining skin health. Alterations in the composition and diversity of the skin microbiome have been associated with a number of dermatological diseases, such as acne, atopic dermatitis, psoriasis and rosacea. The study of the skin microbiome has emerged as a promising area for the development of new therapeutic approaches, offering significant potential for improving the treatment of these conditions. To analyze the implications of the skin microbiome in dermatological diseases, highlighting new therapeutic perspectives based on modulating the microbiome for the management and treatment of these conditions. This is a literature review with a qualitative approach, using the PubMed, Scopus and Web of Science databases to search for scientific articles. Specific descriptors related to the skin microbiome and its influence on health and dermatological diseases were used to refine the search. The time frame covers the years 2019 to 2023, according to the date of the first and last reference selected. The skin microbiome plays a fundamental role in defending the skin against pathogens and modulating the inflammatory response. Dysbiosis, which is the alteration in the composition of the microbiome, has been associated with the development of various dermatological diseases. For example, in acne, an increase in the abundance of *Propionibacterium acnes* has been identified, while in conditions such as atopic dermatitis and psoriasis, a reduction in bacterial diversity appears to contribute to chronic skin inflammation. New therapeutic strategies, such as the use of topical probiotics, prebiotics and treatments that restore the diversity of the microbiome, are being explored as innovative options for treating these conditions. In addition, studies into the use of narrow-spectrum antimicrobials aim to restore microbiological balance without eliminating beneficial bacteria, providing a less aggressive alternative to traditional treatments. Therefore, the study of the skin microbiome has opened up new frontiers for the treatment of dermatological diseases. Modulation of the microbiome offers an innovative and promising therapeutic strategy that can complement conventional treatments, improve clinical results and reduce the side effects associated with topical and systemic treatments. However, more studies are needed to better understand the mechanisms underlying microbiome dysbiosis and how these therapies can be implemented effectively and safely in clinical practice.